Climate change, food security, and socioeconomic livelihood in Pacific Islands - Rosegrant, Mark W.; Valmonte-Santos, Rowena; Thomas, Timothy S.; You, Liangzhi; Chiang, Catherine (Asian Development Bank, 2015)
Climate change projections internationally accepted as being reliable indicate that most countries in the Pacific region will suffer large-scale negative impacts from climate change. These impacts are likely to include elevated air and sea-surface temperatures, increasingly unpredictable rainfall patterns, rising sea levels, and intensification of extreme weather events such as tropical cyclones and El Niño-related droughts. Pacific island countries are particularly vulnerable to such climatic changes, since on average, two-thirds of the region’s population depends on agriculture and fisheries for its livelihood and food security. This is certainly true of at least two of the three countries analyzed under the study on which this report is based, the latter including Fiji, Papua New Guinea (PNG), and Solomon Islands. PNG and Solomon Islands are both vulnerable to the negative impacts of climate change since the percentage share of agriculture in total employment is relatively high in both countries (69% in PNG and 68% in Solomon Islands). Similarly, because of their relatively high percentage share of agriculture in the gross domestic product (GDP) (36% in PNG and 39% in Solomon Islands during 2000-2009), the current capacity of both countries for adapting to climate change is limited.